Pengaruh Perbandingan Tepung Kecambah Kacang Merah (Phaseolus vulgaris L.) dan Tepung Beras Merah (Oryza nivara L.) Terhadap Karakteristik Snack Bar - Natasya Putri, Eazy; Wisaniyasa, Ni Wayan; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This study aims to determine the effect comparison of red bean sprouts flour with red rice flour on the characteristics of snack bar and to determine the proper concentration of red bean sprouts flour and red rice flour that was able to produce snack bar with the best characteristics. The design used in this study was a completely randomized design with treatment comparison of red bean sprouts flour and red rice flour consist of 5 levels, namely: P1 (80%: 20%), P2 (70%: 30%), P3 (60%: 40%), P4 (50%: 50%), and P5 (40%: 60%). Each treatments was repeated 3 times to obtain 15 experimental units. The data were analyzed by analysis of variance and if there treatment was a significant effect, the Duncan Multiple Range Test (DMRT) were perfomed. The result showed that ratio of red bean sprouts flour and red rice flour had a significant effect on water content, ash content, protein content, fat content, crude fiber content, sensori test color, aroma, taste, texture and overall acceptance. the best snack bar characteristics from this research was 50% red bean sprouts flour and 50% red rice flour which had 14.90% water content, 2.64% ash content, 14.16% protein content, 16.19% fat content, 6.71% crude fiber content, 52.10% carbohydrate content, color liked, aroma liked, taste liked with a slightly distinctive taste of red bean, texture liked with slightly crunchy texture and overall acceptance were liked.